Drabovska V. A. Key linguo–cultural concepts of the USA the object of the lexicographic description - Drabovska V. A. (Philological Treatises, 2020)
The article deals with the American nation‟s value and world view bases. The revealed key concepts are considered within the scope of American English linguo–cultural research. Conclusion is made about the possibility to view the linguo–cultural concepts in question as a lexicographic material which should be represented in an American English learner‟s explanatory linguo–cultural dictionary designated for Ukrainian– speaking users.